Cost Recovery Rate Tarif Rumah Sakit dan Tarif INA-CBG’s Berdasarkan Clinical Pathway pada Penyakit Arteri Koroner di RS Pemerintah A di Palembang Tahun 2015 - Mardiah, Mardiah; Rivany, Ronnie (UI Scholars Hub, 2017)
The difference of cost negative in the case of Coronary Artery Disease (CAD) with Percutaneous Coronary Intervention (PCI), indicate health financing gap between of hospital rates and INA-CBG’s rates. This study aimed to see the difference between the cost recovery rate (CRR) of hospital rates and INA-CBG’s rates for CAD with PCI at A Hospital. The results showed that the cost of treatment based on clinical pathways at the severity level I had a higher CRR Hospital rates compared to INA-CBG’s CRR, whereas at the severity level II, Hospital CRR rate was lower than INA-CBG’s CRR for the utility of less than 2 stents. At severity level III, CRR INA-CBGs’ rates with utilization of 1 and 2 stents performed higher rates than the hospitals CRR. This was related to INA-CBG’s rate that did not take the magnitude of the stentulitizationinto account. It is necessary to improve INA-CBG’s tarif development method from hospital base rate to clinical pathway-based cost of treatment in order to meet hospital operational cost and ensure the best quality of service